IMPLEMENTASI KURIKULUM MERDEKA BERBASIS PBL DALAM MENINGKATKAN BERPIKIR KRITIS PADA PESERTA DIDIK DI SDN MOJODADI - Lisa Austina Pratiwi; Khoirotun Nikmah; Anwar Sholikhin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of the Merdeka Curriculum based on Problem Based Learning (PBL) in improving students’ learning activities and learning outcomes at SD Negeri Mojodadi Lamongan. This research employed a kualitatif descriptive approach involving 17 students as the research subjects. Data were collected through observations of student activities and learning outcome tests. The research instruments consisted of student activity observation sheets and learning outcome assessment sheets developed based on PBL learning indicators. The data were analyzed using descriptive analysis techniques by calculating the average scores of students’ activities and learning outcomes. The results showed that the implementation of the Merdeka Curriculum based on PBL was able to increase students’ involvement in the learning process. The average score of student activities reached 83.3, which was categorized as good. Students were actively involved in understanding problems, participating in discussions, collaborating in groups, and expressing opinions during the learning process. In addition, students’ learning outcomes also improved, with an average score of 89 categorized as good to very good. PBL-based learning helped students understand the material more deeply through problem-solving activities and group discussions. Therefore, the implementation of the Merdeka Curriculum based on PBL can be considered an effective learning strategy to improve elementary school students’ learning activities and learning outcomesType the English abstract here, Times New Roman Size 10, spaced 1. Maximum 200 words, in one paragraph without references (references) without abbreviations / acronyms, and without footnotes. Abstracts are written not in the form of mathematics, questions, and conjectures. Abstract contains: research objectives, research methods, analysis techniques and research results.